Experimental investigation on abrasive water jet machining of neem wood plastic composite. (1st June 2022) - Boopathi, Sampath; Thillaivanan, Alagu; Azeem, Mohammed Abdul; Shanmugam, P; Pramod, V R
Abstract: In this article, the neem wood plastic composite material has been fabricated by mixing neem wood saw powder with polypropylene (PP) matrix by injection molding method to study the machining characteristics of the abrasive water jet machining process. The volume percentage of neem wood saw powder, the volume percentage of additive agent talc mixed with PP matrix (A), table traveling speed (Ts), and water-jet pressure (Wp) have been considered as process parameters. The experiments were conducted and analyzed to predict the optimum parameters setting for surface roughness (SR) and kerf angle (KA) using the Taguchi method. It was observed that KA and SR have been greatly impacted by the percentage of neem wood saw powder, table traveling speed, and water-jet pressure. The SR and KA were minimized by reducing the percentage of neem wood powder, table traveling speed, and water-jet pressure. The SR has been decreased by adding talc agent, conversely, the KA has been increased. The concurrent optimum process parameters setting to minimize both SR and KA had been estimated by the weighted product method (WPM). The predicted results from Taguchi and WPM had been verified by microscopic analysis and confirmation experiments.